Lactate shuttling as an allostatic means of thermoregulation in the brain - Kane, Daniel A.; Foo, Alexander C. Y.; Noftall, Erin B.; Brebner, Karen; Marangoni, D. Gerrard (Frontiers in Neuroscience, 2023)
Lactate, the redox-balanced end product of glycolysis, travels within and between cells to fulfill an array of physiologic functions. While evidence for the centrality of this lactate shuttling in mammalian metabolism continues to mount, its application to physical bioenergetics remains underexplored. Lactate represents a metabolic “cul-de-sac,” as it can only re-enter metabolism by first being converted back to pyruvate by lactate dehydrogenase (LDH). Given the differential distribution of lactate producing/consuming tissues during metabolic stresses (e.g., exercise), we hypothesize that lactate shuttling vis-à-vis the exchange of extracellular lactate between tissues serves a thermoregulatory function, i.e., an allostatic strategy to mitigate the consequences of elevated metabolic heat. To explore this idea, the rates of heat and respiratory oxygen consumption in saponin-permeabilized rat cortical brain samples fed lactate or pyruvate were measured. Heat and respiratory oxygen consumption rates, and calorespirometric ratios were lower during lactate vs pyruvate-linked respiration. These results support the hypothesis of allostatic thermoregulation in the brain with lactate.